Sodium-ion battery positive electrode material, preparation method, pole piece and battery

By coating lithium cobalt oxide material on the layered oxide material of the sodium ion battery positive electrode material and forming a high entropy transition layer, the problems of high residual alkali on the surface of the material and the difference in electronic conductivity are solved, and the circulation performance and thermal stability of the material are significantly improved.

CN119764430AActive Publication Date: 2025-04-04FANGCUN NEW ENERGY CO LTD

Patent Information

Application Number
CN202510208539.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-02-25
Publication Date
2025-04-04
Estimated Expiration
2045-02-25

AI Technical Summary

Technical Problem

The existing sodium ion battery positive electrode material layered oxide materials have problems of high surface residual alkali and poor electronic conductivity, which affects its capacity and cycling performance.

Method used

The parent phase and clad structure formed by sodium-electric layered material and lithium-cell cobalt oxide material are adopted to form a high-entropy transition layer through secondary sintering to improve the electronic conductivity and thermal stability of the material.

Benefits of technology

It effectively reduces the residual alkali content of the material, improves the electronic conductivity, enhances the cycling performance and thermal stability of the material, and significantly improves the overall performance of sodium ion batteries.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119764430A_ABST
    Figure CN119764430A_ABST
Patent Text Reader

Abstract

The invention relates to the field of batteries, and particularly discloses a sodium ion battery positive electrode material, a preparation method, a pole piece and a battery. The battery positive electrode material comprises a parent phase formed by a sodium battery layered material and a coating layer coated on the surface of the parent phase and formed by a lithium battery lithium cobalt oxide material, and a specific ion co-doped high-entropy transition layer formed by secondary sintering of the sodium battery layered material and the lithium battery lithium cobalt oxide material is arranged between the coating layer and the parent phase; the composition of the lithium cobalt oxide material of the lithium battery is Li < x > Co < y > M < z > O < 2 >, x < 1 >, y + z = 1, and M is one or more of La, Si, Zr, Nb, Ta and Ti. Compared with a coating technology commonly used in a battery material, the sodium ion battery positive electrode material provided by the invention has the characteristics of low residual alkali, no interlayer cleavage, low powder resistance, high gram capacity exertion, excellent cycle performance and better thermal stability.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the field of batteries, and more specifically, to a sodium ion battery positive electrode material and a preparation method thereof, as well as an electrode sheet and a battery. Background Art

[0002] With the continuous advancement of new energy storage technology, lithium-ion batteries have encountered significant challenges in large-scale energy storage applications due to the scarcity of lithium resources and the continued high price. In contrast, sodium-ion batteries are similar to lithium-ion batteries in terms of operating mechanism, but have better performance in safety and cycle durability, and are more suitable for the needs of the energy storage field. In addition, from the perspective of global resource distribution, sodium resources are abundant and widely distributed, and the overall cost-effectiveness is higher. In view of these factors, sodium-ion batteries have received widespread attention from many new energy companies and are regarded as an ideal option for the next generation of large-scale energy storage technology.

[0003] Sodium-ion batteries have a similar working principle to lithium-ion batteries. Sodium-ion battery systems can be divided into three types according to the type of positive electrode materials: layered oxides, polyanions, and Prussian blue. Among them, layered oxide materials and lithium battery ternary materials have similar two-dimensional layered structures. The battery is charged and discharged through Na + The sodium-ion battery layered oxide material and the lithium-ion battery ternary layered material not only have similar crystal structure types, but also have a processing technology very similar to that of lithium-ion batteries in actual production, which makes them highly replaceable. Therefore, among the three major systems of sodium-ion batteries, the industrialization of layered oxides is more rapid.

[0004] The standard molecular formula of layered oxide materials is Na x MeO2, wherein x is the content of Na in the molecular formula, and Me is a metal ion, generally a transition metal element such as Ni, Fe, Mn, etc. However, when the layered oxide material is actually used, there will be problems of high surface residual alkali and poor electronic conductivity. Among them, the high surface residual alkali is mainly because the interlayer spacing of the sodium-electric layered material is large, the sodium ions in the layer are easily replaced with water molecules in the air, and the sodium ions escaping from the layer form residual alkali on the surface of the material, which not only reduces the capacity of the material, but also deteriorates the processing performance and increases the surface impedance of the material. The poor electronic conductivity is mainly because the powder resistance of the sodium-electric layered material is significantly higher than that of the lithium-electric layered material, which not only increases the impedance and heat generation, but also affects the rate performance. In view of this, the present application proposes a sodium ion battery positive electrode material that can effectively improve the above-mentioned problems. Summary of the invention

[0005] In order to solve the problems of high surface residual alkali and poor electronic conductivity of the existing layered oxide materials as the cathode materials of sodium-ion batteries during actual application, the present application provides a cathode material for sodium-ion batteries, a preparation method, a pole piece, and a battery. This cathode material for sodium-ion batteries has the characteristics of low residual alkali, no interlayer cleavage, low powder resistance, high specific capacity utilization, excellent cycle performance, and better thermal stability.

[0006] The present application adopts the following technical solutions: In the first aspect, the present application provides a cathode material for sodium-ion batteries. The cathode material includes a matrix phase formed by a sodium-based layered material, and a coating layer coated on the surface of the matrix phase and formed by a lithium-based cobaltate material. A high-entropy transition layer formed by secondary sintering of the sodium-based layered material and the lithium-based cobaltate material is provided between the coating layer and the matrix phase; The composition of the sodium-based layered material is Na a A b Ni c B d O2, where 0 < a + b ≤ 1, c + d = 1; wherein, A is one or more of Li, K, Ca, La, and B is one or more of V, Cr, Mn, Fe, Co, Ga, Sn, Zr, Nb, Ta.

[0007] The composition of the lithium-based cobaltate material is Li x Co y M z O2, where 0 < x ≤ 1, y + z = 1, where M is one or more of La, Si, Zr, Nb, Ta, Ti.

[0008] Furthermore, the coating layer is 0.2 - 3 wt% of the mass of the matrix phase;

[0009] Furthermore, the above M is at least one of Zr, Nb, Ti.

[0010] Furthermore, the above B includes Fe element, and a combination formed with at least one of Mn, Zr, Sn.

[0011] Furthermore, in the lithium-based cobaltate material, the value range of z is 0 ≤ z ≤ 0.05; in the sodium-based layered material, the value range of b is 0 ≤ b ≤ 0.05, and the value range of c is 0 ≤ c ≤ 0.8.

[0012] Preferably, the composition of the lithium-based cobaltate material is Li x Co y M zO₂, where 0.94 ≤ x ≤ 0.96, y + z = 1, 0.96 ≤ y ≤ 0.98, and M is either Zr alone, or Nb, or Nb + Ti, or Nb + Zr.

[0013] Preferably, the composition of the above sodium-ion layered material is Na a A b Ni c B d O₂, where 0 < a + b ≤ 1, c + d = 1; where 0.94 ≤ a ≤ 0.97, and A is one or more of Li, Ca, and La; 0.33 ≤ c ≤ 0.40, B is the Fe + Mn element, or B is a combination formed by at least one of the Fe and Mn elements and Zr and Sn.

[0014] In a second aspect, the present application provides a method for preparing the above sodium-ion battery cathode material, which includes: (1) Mixing the precursor powder of the sodium-ion layered material, a sodium source, and an additive, and then performing a first sintering to obtain a mother phase; (2) Mixing the mother phase with a solution containing a cobalt salt and a sodium source, and obtaining a composite material with a cobalt-coated surface through a precipitation reaction; then uniformly mixing the composite material with a lithium source and a doping additive containing the M element according to the stoichiometric ratio, and performing a second sintering to obtain the sodium-ion battery cathode material.

[0015] Preferably, the precursor powder in step (1) is obtained by co-precipitation reaction of a metal sulfate solution, a precipitating agent, and a complexing agent according to the stoichiometric ratio, followed by aging, filtration, washing, and drying.

[0016] Among them, the sulfate in the metal sulfate solution is selected from nickel sulfate, and one or more of aluminum sulfate, magnesium sulfate, titanium oxysulfate, manganese sulfate, ferrous sulfate, cobalt sulfate, copper sulfate, and zinc sulfate. The precipitating agent is an alkaline sodium source solution, such as one or more of sodium carbonate, sodium bicarbonate, and sodium hydroxide. The complexing agent is ammonia water or other alkaline solutions.

[0017] Preferably, the additive in step (1) is a doping additive, including one or more of lithium carbonate, lithium hydroxide monohydrate, vanadium pentoxide, chromium trioxide, gallium trioxide, tin dioxide, zirconium dioxide, niobium pentoxide, and tantalum pentoxide.

[0018] Further, the cobalt salt in step (2) is selected from one or more of cobalt nitrate, cobalt sulfate, and cobalt chloride; the alkaline sodium source is one or more of sodium carbonate, sodium bicarbonate, and sodium hydroxide; the lithium source is one or more of lithium carbonate, lithium hydroxide monohydrate, and lithium bicarbonate.

[0019] Furthermore, the doping additive containing the M element is one or more of lanthanum trioxide, titanium dioxide, silicon dioxide, zirconium dioxide, niobium pentoxide, and tantalum pentoxide.

[0020] Furthermore, the sintering temperature of the first sintering and the second sintering is 800-1000° C., and the sintering time is 6-18 hours.

[0021] Preferably, the sintering temperature is 850-950°C and the sintering time is 6-14h; More preferably, the sintering temperature of the first sintering is 870-950° C., and the sintering time is 10-12 h; the sintering temperature of the second sintering is 820-870° C., and the sintering time is 6-12 h.

[0022] In a third aspect, the present application provides a positive electrode plate, in which the positive electrode active slurry includes the above-mentioned sodium ion battery positive electrode material.

[0023] In a fourth aspect, the present application provides a sodium ion battery comprising the above-mentioned positive electrode plate.

[0024] In summary, this application has the following beneficial effects: The sodium ion battery positive electrode material provided in the present application has a parent phase and a coating layer. Compared with the coating technology commonly used in battery materials, the coating layer material of the present application is Li x Co y M z O2, which is a lithium cobalt oxide material similar to the positive electrode of lithium battery, also has a layered structure, is similar to the crystal material of the parent phase, has better lattice matching, and has better interface bonding and compatibility with the parent phase. During the long cycle process, it can always maintain a good coating effect on the parent phase material, effectively suppress volume strain and interlayer cleavage phenomenon, and ensure better capacity retention and cycle life. At the same time, the lithium cobalt oxide material of the lithium battery as the coating layer material has excellent electronic conductivity, while the parent phase sodium battery layered positive electrode material itself has poor electronic conductivity and high powder resistance. The use of lithium cobalt oxide for surface coating can effectively improve the powder resistance of the parent phase material.

[0025] In the process of preparing the sodium ion battery positive electrode material provided by the present application, the composite material coated with cobalt on the surface of the parent phase is mixed with a lithium source and a doping additive containing the M element for secondary sintering. During the second sintering process, the residual alkali remaining on the surface will enter the parent phase material or combine with the surface coating material, effectively reducing the amount of residual alkali. At the same time, the raw material lithium source in the coating layer material has a lower melting point, and during the high-temperature reaction process of the secondary sintering, the sharp edges and corners on the surface of the parent phase layered material are effectively reduced, and the overall particles become more rounded, so the compaction density of the powder is further improved.

[0026] In a preferred embodiment of the present application, by selectively doping specific metals in the coating layer and the parent phase, the replacement of Na+ ions with water molecules in the air can be effectively blocked, thereby effectively improving the hygroscopic stability of the material; at the same time, both the parent phase material and the coating material are combinedly doped, and during the high-temperature reaction process of the secondary sintering, a locally mixed transition zone is formed at the interface between the parent phase and the coating layer, which effectively reduces the activity of free lattice oxygen, and the thermal stability of the resulting material is significantly improved. BRIEF DESCRIPTION OF THE DRAWINGS

[0027] Figure 1 It is a schematic structural diagram of the sodium electrode layered positive electrode material with a coating layer provided by the present invention.

[0028] Figure 2 These are scanning electron microscope microscopic morphology images of the coated sodium-electrolyte layered positive electrode material prepared in Example 1 of the present invention and the uncoated parent phase positive electrode material sample prepared in Comparative Example 1.

[0029] Figure 3 The coated sodium-ion layered positive electrode material prepared in Example 1 of the present invention and the uncoated parent phase positive electrode material sample prepared in Comparative Example 1 are scanning electron microscope microscopic morphology images of the particles after 50 power cycles.

[0030] Figure 4 The coated sodium-based layered cathode material prepared in Example 1 of the present invention and the uncoated mother phase cathode material sample prepared in Comparative Example 1 are compared in the cycle curves measured in the voltage range of 2 to 4 V with a charge and discharge rate of 0.5 C and a voltage of 1 C. DETAILED DESCRIPTION

[0031] The embodiments of the present invention will be described in detail below in conjunction with examples. However, those skilled in the art will understand that the following examples are only used to illustrate the present invention and should not be construed as limiting the scope of the present invention. The specific conditions not specified in the examples are carried out according to conventional conditions or conditions recommended by the manufacturer. The reagents or instruments used without indicating the manufacturer are all conventional products that can be purchased commercially.

[0032] The specific embodiments of the present invention are described in detail below. It should be understood that the specific embodiments described herein are only used to illustrate and explain the present invention, and are not used to limit the present invention.

[0033] Example 1 This embodiment provides a sodium ion battery positive electrode material, Figure 1 It is a structural diagram, and the compositions of the parent phase and the coating layer are:

[0034] Mother phase: Na 0.97 La 0.01 (Ni 0.33 Fe0.33 Mn 0.32 Sn 0.01 )O2, Coating layer: Li 0.96 Co 0.96 Zr 0.04 O2; The preparation method is as follows: (1) Preparation of parent layered oxide Nickel sulfate, ferrous sulfate, and manganese sulfate were weighed in a molar ratio of 0.33:0.33:0.32, and dissolved in deionized water to prepare a 2 mol / L soluble metal salt solution. NaOH was prepared into a 5 mol / L solution as a precipitant, and ammonia water was prepared into a 5 mol / L solution as a complexing agent. The metal salt solution, precipitant, and complexing agent were added to the precipitation reactor at a certain flow rate, and after complete reaction, they were aged and allowed to stand for 12 hours, and then filtered, washed, and dried to obtain a hydroxide precursor powder. The above-mentioned precursor powder was weighed with sodium carbonate, lanthanum oxide, and tin dioxide ultrafine powder according to the molar ratio of Na:La:Ni:Fe:Mn:Sn=0.97:0.01:0.33:0.33:0.32:0.01, and then mixed at high speed, sintered at 900°C in an air atmosphere for 12 hours, and the parent phase positive electrode material was obtained after cooling.

[0035] (2) Preparation of surface coating The designed coating mass is 1.5wt% of the mass of the parent phase positive electrode material. Weigh 100g of the parent phase positive electrode material and add it to ethanol for stirring and dispersion. Weigh 2.3026g of cobalt sulfate and add a certain amount of deionized water to prepare a 2mol / L cobalt sulfate solution. Add the cobalt sulfate solution to the ethanol solution of the parent phase material under stirring and disperse it evenly. Add 5mol / L sodium hydroxide aqueous solution at a certain flow rate for precipitation reaction. After the reaction is completed, the cobalt hydroxide-coated positive electrode material is obtained by filtering, washing and drying. Weigh 100g of the cobalt hydroxide-coated positive electrode material, and weigh 0.5388g of ultrafine lithium carbonate and 0.0749g of ultrafine zirconium dioxide at the same time for high-speed mixing, and then sinter at 850℃ in an air atmosphere for 8h. After cooling, the coated sodium-electric layered positive electrode material is obtained.

[0036] Example 2 This embodiment provides a sodium ion battery positive electrode material, wherein the compositions of the parent phase and the coating layer are respectively: Mother phase: Na 0.94 Ca 0.03 (Ni 0.33 Fe 0.26 Mn 0.39 Zr 0.01 )O2, Coating layer: Li 0.96 Co0.98 Nb 0.02 O2; The preparation method is as follows: (1) Preparation of parent layered oxide Nickel sulfate, ferrous sulfate and manganese sulfate were weighed in a molar ratio of 0.33:0.26:0.39 and dissolved in deionized water to prepare a 2 mol / L soluble metal salt solution. NaOH was prepared into a 5 mol / L solution as a precipitant, and ammonia water was prepared into a 5 mol / L solution as a complexing agent. The metal salt solution, precipitant and complexing agent were added to the precipitation reactor at a certain flow rate, and after complete reaction, they were aged and allowed to stand for 12 hours, and then filtered, washed and dried to obtain a hydroxide precursor powder. The above-mentioned precursor powder was weighed with sodium carbonate, calcium carbonate and zirconium dioxide ultrafine powder according to the molar ratio of Na:Ca:Ni:Fe:Mn:Zr=0.94:0.03:0.33:0.26:0.39:0.01, and then mixed at high speed, sintered at 950°C in an air atmosphere for 12 hours, and the parent phase positive electrode material was obtained after cooling.

[0037] (2) Preparation of surface coating The designed coating mass is 1wt% of the mass of the parent phase positive electrode material. Weigh 100g of the parent phase positive electrode material and add it to ethanol for stirring and dispersion. Weigh 100g of the parent phase positive electrode material and add it to ethanol for stirring and dispersion. Weigh 1.5677g of cobalt sulfate and add a certain amount of deionized water to prepare a 2mol / L cobalt sulfate solution. Add the cobalt sulfate solution to the ethanol solution of the parent phase material under stirring and disperse it evenly. Add 5mol / L sodium hydroxide aqueous solution at a certain flow rate for precipitation reaction. After the reaction is completed, the cobalt hydroxide coated positive electrode material is obtained by filtering, washing and drying. Weigh 100g of the cobalt hydroxide coated positive electrode material, and weigh 0.3607g of ultrafine lithium carbonate and 0.0271g of ultrafine niobium pentoxide at the same time for high-speed mixing, and then sinter at 870℃ in an air atmosphere for 6h. After cooling, the coated sodium electric layered positive electrode material is obtained.

[0038] Example 3 This embodiment provides a sodium ion battery positive electrode material, wherein the compositions of the parent phase and the coating layer are respectively: Mother phase: Na 0.94 La 0.02 (Ni 0.33 Fe 0.33 Mn 0.32 Zr 0.005 Sn 0.005 )O2, Coating layer: Li 0.94 Co 0.96 Ti 0.02 Nb 0.02 O2; The preparation method is as follows: (1) Preparation of parent layered oxide Nickel sulfate, ferrous sulfate and manganese sulfate were weighed in a molar ratio of 0.33:0.33:0.32, and dissolved in deionized water to prepare a 2 mol / L soluble metal salt solution. NaOH was prepared into a 5 mol / L solution as a precipitant, and ammonia water was prepared into a 5 mol / L solution as a complexing agent. The metal salt solution, precipitant and complexing agent were added to the precipitation reactor at a certain flow rate, and after complete reaction, they were aged and stood for 12 hours, and then filtered, washed and dried to obtain a hydroxide precursor powder. The above-mentioned precursor powder was weighed with sodium carbonate, lanthanum oxide, zirconium dioxide and tin dioxide ultrafine powder according to the molar ratio of Na:La:Ni:Fe:Mn:Zr:Sn=0.94:0.02:0.33:0.33:0.32:0.005:0.005, and then mixed at high speed, sintered at 930°C in an air atmosphere for 10 hours, and the parent phase positive electrode material was obtained after cooling.

[0039] (2) Preparation of surface coating The designed coating mass is 3wt% of the mass of the parent phase positive electrode material. Weigh 100g of the parent phase positive electrode material and add it to ethanol for stirring and dispersion. Weigh 4.6072g of cobalt sulfate and add a certain amount of deionized water to prepare a 2mol / L cobalt sulfate solution. Add the cobalt sulfate solution to the ethanol solution of the parent phase material under stirring and disperse it evenly. Add 5mol / L sodium hydroxide aqueous solution at a certain flow rate for precipitation reaction. After the reaction is completed, the cobalt hydroxide-coated positive electrode material is obtained by filtering, washing and drying. Weigh 100g of the cobalt hydroxide-coated positive electrode material, and weigh 1.0411g of ultrafine lithium carbonate, 0.0479g of ultrafine titanium dioxide, and 0.0797g of ultrafine niobium pentoxide powder at the same time for high-speed mixing, and then sinter at 820℃ in an air atmosphere for 10h, and obtain the coated sodium electric layered positive electrode material after cooling.

[0040] Example 4 This embodiment provides a sodium ion battery positive electrode material, wherein the compositions of the parent phase and the coating layer are respectively: Mother phase: Na 0.95 Li 0.03 Ca 0.01 (Ni 0.40 Fe 0.20 Mn 0.40 )O2, Coating layer: Li 0.95 Co 0.97 Zr 0.01 Nb 0.02 O2; (1) Preparation of parent layered oxide Nickel sulfate, ferrous sulfate and manganese sulfate were weighed in a molar ratio of 0.40:0.20:0.40, and dissolved in deionized water to prepare a 2 mol / L soluble metal salt solution. NaOH was prepared into a 5 mol / L solution as a precipitant, and ammonia water was prepared into a 5 mol / L solution as a complexing agent. The metal salt solution, precipitant and complexing agent were added to the precipitation reactor at a certain flow rate, and after complete reaction, they were aged and stood for 12 hours, and then filtered, washed and dried to obtain the hydroxide precursor powder. The above-mentioned precursor powder was weighed with sodium carbonate, lithium carbonate and calcium carbonate ultrafine powder according to the molar ratio of Na:Li:Ca:Ni:Fe:Mn=0.95:0.03:0.01:0.40:0.20:0.40, and then mixed at high speed, sintered at 870°C in an air atmosphere for 12 hours, and the parent phase positive electrode material was obtained after cooling.

[0041] (2) Preparation of surface coating The designed coating mass is 2wt% of the mass of the parent phase positive electrode material. Weigh 100g of the parent phase positive electrode material and add it to ethanol for stirring and dispersion. Weigh 3.1035g of cobalt sulfate and add a certain amount of deionized water to prepare a 2mol / L cobalt sulfate solution. Add the cobalt sulfate solution to the ethanol solution of the parent phase material under stirring and disperse it evenly. Add 5mol / L sodium hydroxide aqueous solution at a certain flow rate for precipitation reaction. After the reaction is completed, the cobalt hydroxide-coated positive electrode material is obtained by filtering, washing and drying. Weigh 100g of the cobalt hydroxide-coated positive electrode material, and weigh 0.7076g of ultrafine lithium carbonate, 0.0248g of ultrafine zirconium dioxide, and 0.0536g of ultrafine niobium pentoxide powder at the same time for high-speed mixing, and then sinter at 830℃ in an air atmosphere for 12h, and obtain the coated sodium electric layered positive electrode material after cooling.

[0042] Example 5 This embodiment provides a sodium ion battery positive electrode material, wherein the compositions of the parent phase and the coating layer are respectively: Mother phase: Na 0.95 K 0.03 La 0.01 (Ni 0.33 Fe 0.33 Mn 0.32 V 0.005 Ga 0.005 )O2, Coating layer: Li 0.95 Co 0.97 Si 0.01 Ta 0.02 O2; (1) Preparation of parent layered oxide Nickel sulfate, ferrous sulfate, and manganese sulfate were weighed in a molar ratio of 0.33:0.33:0.32, and dissolved in deionized water to prepare a 2 mol / L soluble metal salt solution. NaOH was prepared into a 5 mol / L solution as a precipitant, and ammonia water was prepared into a 5 mol / L solution as a complexing agent. The metal salt solution, precipitant, and complexing agent were added to the precipitation reactor at a certain flow rate, and after complete reaction, they were aged and allowed to stand for 12 hours, and then filtered, washed, and dried to obtain a hydroxide precursor powder. The above-mentioned precursor powder was weighed with sodium carbonate, lithium carbonate, and calcium carbonate ultrafine powders in a molar ratio of Na:K:La:Ni:Fe:Mn:V:Ga=0.95:0.03:0.01:0.33:0.33:0.32:0.005:0.005, and then mixed at high speed, sintered at 870°C in an air atmosphere for 12 hours, and cooled to obtain the parent phase positive electrode material.

[0043] (2) Preparation of surface coating The designed coating mass is 2wt% of the mass of the parent phase positive electrode material. Weigh 100g of the parent phase positive electrode material and add it to ethanol for stirring and dispersion. Weigh 3.1035g of cobalt sulfate and add a certain amount of deionized water to prepare a 2mol / L cobalt sulfate solution. Add the cobalt sulfate solution to the ethanol solution of the parent phase material under stirring and disperse it evenly. Add 5mol / L sodium hydroxide aqueous solution at a certain flow rate for precipitation reaction. After the reaction is completed, filter, wash and dry to obtain a cobalt hydroxide-coated positive electrode material. Weigh 100g of the cobalt hydroxide-coated positive electrode material, and weigh ultrafine lithium carbonate, ultrafine tantalum pentoxide powder, and ultrafine silicon dioxide powder according to the molar ratio for high-speed mixing, then sinter at 800℃ in an air atmosphere for 18h, and obtain the coated sodium electric layered positive electrode material after cooling.

[0044] Example 6 This embodiment provides a sodium ion battery positive electrode material, wherein the compositions of the parent phase and the coating layer are respectively: Mother phase: Na 0.97 La 0.01 (Ni 0.33 Fe 0.32 Mn 0.32 Co 0.01 Ta 0.01 )O2, Coating layer: Li 0.95 Co 0.97 Zr 0.01 Nb 0.02 O2; (1) Preparation of parent layered oxide Nickel sulfate, ferrous sulfate and manganese sulfate were weighed in a molar ratio of 0.33:0.32:0.32, and dissolved in deionized water to prepare a 2 mol / L soluble metal salt solution. NaOH was prepared into a 5 mol / L solution as a precipitant, and ammonia water was prepared into a 5 mol / L solution as a complexing agent. The metal salt solution, precipitant and complexing agent were added to the precipitation reactor at a certain flow rate, and after complete reaction, they were aged and stood for 12 hours, and then filtered, washed and dried to obtain the hydroxide precursor powder. The above-mentioned precursor powder was weighed with sodium carbonate, lithium carbonate and calcium carbonate ultrafine powder according to the molar ratio of Na:La:Ni:Fe:Mn:Co:Ta=0.97:0.01:0.33:0.32:0.32:0.01:0.01, and then mixed at high speed, sintered at 1000°C for 6 hours in an air atmosphere, and the parent phase positive electrode material was obtained after cooling.

[0045] (2) Preparation of surface coating The designed coating mass is 0.25wt% of the mass of the parent phase positive electrode material. Weigh 100g of the parent phase positive electrode material and add it to ethanol for stirring and dispersion. Weigh 3.1035g of cobalt sulfate and add a certain amount of deionized water to prepare a 2mol / L cobalt sulfate solution. Add the cobalt sulfate solution to the ethanol solution of the parent phase material under stirring and disperse it evenly. Add 5mol / L sodium hydroxide aqueous solution at a certain flow rate for precipitation reaction. After the reaction is completed, the positive electrode material coated with cobalt hydroxide is obtained by filtering, washing and drying. Weigh 100g of the positive electrode material coated with cobalt hydroxide, and weigh 0.7076g of ultrafine lithium carbonate, 0.0248g of ultrafine zirconium dioxide, and 0.0536g of ultrafine niobium pentoxide powder at the same time for high-speed mixing, and then sinter at 830℃ in an air atmosphere for 12h, and obtain the coated sodium electric layered positive electrode material after cooling.

[0046] Example 7 This embodiment provides a sodium ion battery positive electrode sheet, and the preparation method thereof includes: The coated sodium-electrolyte layered positive electrode material prepared in any one of Examples 1-6 was mixed with a binder and conductive carbon black in a mass ratio of 94:3:3, dissolved in N-methylpyrrolidone, and after sufficient stirring and degassing, filtered to obtain a positive electrode slurry.

[0047] The positive electrode slurry is coated on the surface of the current collector aluminum foil by an automatic coating machine, and then the coated electrode is dried at 105° C. for more than 12 hours under blowing and vacuum conditions, and the positive electrode of the sodium ion battery is obtained after roller pressing.

[0048] Example 8 This embodiment provides a sodium ion battery, and the preparation method thereof includes: The positive electrode provided in Example 7 was punched into a disc with a diameter of 12 mm, the negative electrode was a metallic sodium sheet, a glass fiber membrane was used as a diaphragm, and the electrolyte was 1 mol / L NaPF6 dissolved in a mixed solvent of ethylene carbonate and diethyl carbonate (EC:DEC=1:1). The sodium ion battery was assembled in an argon protective glove box with a water and oxygen content of less than 1 ppm.

[0049] Comparative Example 1 This comparative example prepares an uncoated sodium layered positive electrode material, the composition of which is Na 0.97 La 0.01 (Ni 0.33 Fe 0.33 Mn 0.32 Sn 0.01 )O2, the preparation method is the same as Example 1.

[0050] Comparative Example 2 This comparative example prepares an uncoated sodium layered positive electrode material, the composition of which is Na 0.94 Ca 0.03 (Ni 0.33 Fe 0.26 Mn 0.39 Zr 0.01 )O2, the preparation method is the same as Example 2.

[0051] Comparative Example 3 This comparative example prepares an uncoated sodium layered positive electrode material, the composition of which is Na(Ni 0.33 Fe 0.33 Mn 0.33 )O2, the preparation method is as follows: Nickel sulfate, ferrous sulfate, and manganese sulfate were weighed in a molar ratio of 0.33:0.33:0.33, and dissolved in deionized water to prepare a 2 mol / L soluble metal salt solution. NaOH was prepared into a 5 mol / L solution as a precipitant, and ammonia water was prepared into a 5 mol / L solution as a complexing agent. The metal salt solution, precipitant, and complexing agent were added to the precipitation reactor at a certain flow rate, and after complete reaction, they were aged and allowed to stand for 12 hours, and then filtered, washed, and dried to obtain a hydroxide precursor powder. The above-mentioned precursor powder and sodium carbonate ultrafine powder were weighed in a molar ratio of Na:Ni:Fe:Mn=1:0.33:0.33:0.33, mixed evenly at high speed, sintered at 930°C in an air atmosphere for 10 hours, and cooled to obtain the parent phase positive electrode material.

[0052] Comparative Example 4 This comparative example prepares an uncoated sodium layered positive electrode material, the composition of which is Na(Ni 0.4 Fe 0.2 Mn 0.4 )O2, the preparation method is as follows: Nickel sulfate, ferrous sulfate and manganese sulfate were weighed in a molar ratio of 0.40:0.20:0.40, and dissolved in deionized water to prepare a 2 mol / L soluble metal salt solution. NaOH was prepared into a 5 mol / L solution as a precipitant, and ammonia water was prepared into a 5 mol / L solution as a complexing agent. The metal salt solution, precipitant and complexing agent were added to the precipitation reactor at a certain flow rate, and after complete reaction, they were aged and allowed to stand for 12 hours, and then filtered, washed and dried to obtain the hydroxide precursor powder. The above precursor powder and sodium carbonate ultrafine powder were weighed in a molar ratio of Na:Ni:Fe:Mn:Zr=1:0.40:0.20:0.40, mixed evenly at high speed, sintered at 870°C in an air atmosphere for 12 hours, and cooled to obtain the parent phase positive electrode material.

[0053] Comparative Example 5 This comparative example provides a sodium ion battery positive electrode material, the compositions of the parent phase and the coating layer are respectively: Mother phase: Na 0.97 La 0.01 (Ni 0.33 Fe 0.33 Mn 0.32 Sn 0.01 )O2, Coating layer: Li 0.96 Co 1.00 O2; The preparation method thereof comprises: The parent layered oxide is prepared in the same manner as in Example 1.

[0054] Preparation of surface coating: The designed coating mass is 1.5wt% of the mass of the parent phase positive electrode material. Weigh 100g of the parent phase positive electrode material and add it to ethanol for stirring and dispersion. Weigh 2.3026g of cobalt sulfate and add a certain amount of deionized water to prepare a 2mol / L cobalt sulfate solution. Add the cobalt sulfate solution to the ethanol solution of the parent phase material under stirring and disperse it evenly. Add 5mol / L sodium hydroxide aqueous solution at a certain flow rate for precipitation reaction. After the reaction is completed, filter, wash and dry to obtain a cobalt hydroxide-coated positive electrode material. Weigh 100g of the cobalt hydroxide-coated positive electrode material, and weigh ultrafine lithium carbonate at the same time for high-speed mixing, then sinter at 850℃ for 8h in an air atmosphere, and obtain the coated sodium-electric layered positive electrode material after cooling.

[0055] Comparative Example 6 This comparative example provides a sodium ion battery positive electrode material, the compositions of the parent phase and the coating layer are respectively: Mother phase: Na 0.97 La 0.01 (Ni 0.33 Fe0.33 Mn 0.32 Sn 0.01 )O2, Coating layer: Cr 0.96 P 0.04 O2; The preparation method thereof comprises: The parent layered oxide is prepared in the same manner as in Example 1.

[0056] Preparation of surface coating layer: prepared according to existing methods.

[0057] Comparative Example 7 This comparative example provides a sodium ion battery positive electrode material, the compositions of the parent phase and the coating layer are respectively: Mother phase: Na 0.98 (Ni 0.33 Fe 0.33 Mn 0.32 Sn 0.01 )O2, Coating layer: Li 0.96 Co 0.96 Zr 0.04 O2; The preparation method is as follows: (1) Preparation of parent layered oxide Nickel sulfate, ferrous sulfate, and manganese sulfate were weighed in a molar ratio of 0.33:0.33:0.32, and dissolved in deionized water to prepare a 2 mol / L soluble metal salt solution. NaOH was prepared into a 5 mol / L solution as a precipitant, and ammonia water was prepared into a 5 mol / L solution as a complexing agent. The metal salt solution, precipitant, and complexing agent were added to the precipitation reactor at a certain flow rate, and after complete reaction, they were aged and allowed to stand for 12 hours, and then filtered, washed, and dried to obtain a hydroxide precursor powder. The above-mentioned precursor powder was weighed with sodium carbonate, lanthanum oxide, and tin dioxide ultrafine powder according to the molar ratio of Na:Ni:Fe:Mn:Sn=0.98:0.33:0.33:0.32:0.01, and then mixed at high speed, sintered at 900°C in an air atmosphere for 12 hours, and the parent phase positive electrode material was obtained after cooling.

[0058] (2) Preparation of surface coating layer: same as in Example 1.

[0059] Performance testing

[0060] Detection Methods 1. Scanning electron microscopy: The materials provided in the embodiments and comparative examples were subjected to scanning electron microscopy to observe the material morphology.

[0061] 2. Button cell production: The positive electrode material, adhesive PVDF and conductive carbon black (Super P) are mixed in a ratio of 94:3:3 and dissolved in the solvent NMP. After sufficient stirring and degassing, the slurry is filtered to obtain a slurry. The obtained slurry is coated on the surface of the current collector aluminum foil using an automatic coating machine. The coated electrode is dried at 105°C for more than 12 hours under blast and vacuum conditions, and the positive electrode is obtained after roller pressing. The positive electrode is punched into a disc with a diameter of 12mm, the negative electrode is a metal sodium sheet, the glass fiber membrane is used as a diaphragm, and the electrolyte is 1mol / L NaPF6 dissolved in an organic solution of EC:DEC=1:1. The CR2032 button cell is assembled in an argon protection glove box with a water and oxygen content of less than 1ppm. The battery charge and discharge current of 1C is 120mA / g, and the cycle curve is detected in the voltage range of 2~4V.

[0062] 3. Powder resistance test: Weigh a certain amount of powder sample and put it into a cylindrical mold. Apply pressure to press the powder into a dense disc. The die punch has a gold-plated surface to ensure electrical contact. Maintain the pressure for a certain period of time at the maximum pressure of 1T and read the resistance value.

[0063] 4. Compaction density test: Weigh a certain amount of powder sample and put it into a cylindrical mold. Apply pressure to compress the powder into a disc shape. After maintaining the pressure at 3T for a certain period of time, read the volume of the compressed material and obtain the powder compaction density through the mass-to-volume ratio.

[0064] 5. Thermal stability determination: Disassemble the button cell fully charged to 4.0V, take out the positive electrode, soak it in solvent, scrape the powder on the surface of the electrode and load it into the thermogravimetric-differential thermal analysis linkage equipment, heat it to 550℃ in a nitrogen atmosphere and test the DSC exothermic curve.

[0065] 6. Air exposure test: Weigh a certain amount of powder and put it into a ziplock bag, expose it to normal air for 72 hours, and test the difference in water content before and after exposure.

[0066] (II) Test results As shown in Table 1 and Figure 2-4 As shown: Depend on Figure 2 It can be seen that in the electron microscope image of the uncoated and first-fired sample (Comparative Example 1) on the left, the particles are flaky with sharp edges and corners; in the electron microscope image of the coated and second-fired sample (Example 1) on the right, the particles are relatively rounded. This shows that the sodium-based layered positive electrode material provided by the present application, after surface coating and high-temperature secondary sintering, makes the parent material more rounded, the particles grow again, and the overall compaction density is improved.

[0067] Depend on Figure 3It can be seen that in the electron microscope image of the sample after the cycle without coating and firing once (Comparative Example 1) on the left, the particles showed interlayer cleavage after multiple cycles; in the electron microscope image of the sample after the cycle after coating and firing twice (Example 1) on the right, the particles remained intact after multiple cycles without obvious cleavage.

[0068] Depend on Figure 4 It can be seen that under the conditions of 0.5C charge and 1C discharge, as the number of cycles increases, the cycle capacity retention rate of the sample after coating and modification (Example 1) is significantly higher than that of the sample without coating and modification (Comparative Example 1).

[0069] Depend on Figure 3 , Figure 4 It can be explained that the surface coating layer of the sodium-based layered positive electrode material provided in the present application can effectively inhibit stress release during the cycle, weaken the interlayer cleavage of the particles, stabilize the interface film on the surface of the active material in the battery, and improve the cycle performance.

[0070] The test results of the materials obtained in Examples 1-6 and Comparative Examples 1-7 of the present application are shown in Table 1:

[0071] In combination with Example 1-2 and Comparative Example 1-2, it can be seen that the excellent electronic conductivity of lithium cobalt oxide reduces the powder resistance of the overall material by coating the surface coating layer outside the parent layered oxide; and in the process of preparing the coating layer, after high-temperature secondary sintering, the intermediate transition layer formed at the interface junction has multiple atoms coexisting, so a local high-entropy region is formed at the interface, which, on the one hand, hinders the replacement of sodium ions with water molecules in the air, thereby improving the hygroscopic stability of the material, and on the other hand, inhibits the activity of free lattice oxygen, thereby improving the thermal stability of the material; at the same time, the cycle performance of the battery is also greatly improved.

[0072] Combining Comparative Examples 1-2 and Comparative Examples 3-4, it can be seen that even if no coating is performed, due to the fact that Comparative Examples 1-2 have Na (Ni 0.33 Fe 0.33 Mn 0.33 )O2 or Na(Ni 0.4 Fe 0.2 Mn 0.4 )O2 is doped with other elements (La+Sn; or Ca+Zr), and the hygroscopic performance of the obtained sodium-electrode layered positive electrode material is significantly improved. This shows that the parent phase formed by the sodium-electrode layered material in the present application has excellent hygroscopic stability.

[0073] In combination with Example 1 and Comparative Examples 5-6, it can be seen that in the case of coating, due to the different materials of the coating layer, the obtained positive electrode materials also show very large differences. Relative to Comparative Examples 5-6, the present application uses lithium cobalt oxide with a similar structure as the coating layer and dopes it, which not only ensures better interface bonding with the parent phase material, but also further enhances the thermal stability, hygroscopic stability and cycle performance of the material. When the lithium cobalt oxide of the coating layer is undoped, as shown in Comparative Example 5, the structure and thermal stability of the coating layer itself are relatively poor, resulting in poor circulation of the final material and insufficient thermal stability. When the coating layer is other substances, as shown in Comparative Example 6, the final material capacity is low, the powder resistance is very high, and the cycle performance is relatively poor.

[0074] Combining Example 1 and Comparative Example 7, it can be seen that when the same coating is performed, since the sodium ion position of the parent phase material is not doped and modified, the sodium ions of the sodium layer are relatively more hygroscopic and replaced with water molecules. The corresponding material absorbs water severely after exposure and has poor cycle performance.

[0075] This specific embodiment is merely an explanation of the present application and is not a limitation of the present application. After reading this specification, those skilled in the art may make modifications to the present embodiment without any creative contribution as needed, but such modifications are protected by the patent law as long as they are within the scope of the claims of the present application.

Claims

1. A sodium ion battery positive electrode material, characterized in that: The positive electrode material comprises a parent phase formed by a sodium-electrolyte layered material, and a coating layer formed by a lithium-electrolyte cobalt oxide material and coated on the surface of the parent phase, wherein a transition layer formed by secondary sintering of the sodium-electrolyte layered material and the lithium-electrolyte cobalt oxide material is provided between the coating layer and the parent phase; The composition of the sodium-based layered material is Na a A b Ni c B d O2, where 0 < a + b ≤ 1 and c + d = 1; wherein, A is one or more of Li, K, Ca, and La, and B is one or more of V, Cr, Mn, Fe, Co, Ga, Sn, Zr, Nb, and Ta; The composition of the lithium cobaltate material is Li x Co y M z O2, where 0 < x ≤ 1, y + z = 1, and M is one or more of La, Si, Zr, Nb, Ta, and Ti.

2. The sodium ion battery positive electrode material according to claim 1, characterized in that The M is at least one of Zr, Nb and Ti.

3. The sodium ion battery positive electrode material according to claim 1, characterized in that The B includes Fe element and a combination thereof with at least one of Mn, Zr and Sn.

4. The sodium ion battery positive electrode material according to claim 1, characterized in that In the lithium cobalt oxide material, the value range of z is 0≤z≤0.05; in the sodium electrode layered material, the value range of b is 0≤b≤0.05, and the value range of c is 0≤c≤0.

8.

5. A method for preparing a positive electrode material for a sodium ion battery according to any one of claims 1 to 4, characterized in that: It includes: After mixing the precursor powder of the sodium electric layered material, the sodium source and the additive, the mixture is sintered for the first time to obtain a parent phase; The parent phase is mixed with a solution containing a cobalt salt and a sodium source, and a composite material with a surface coated with cobalt is obtained after a precipitation reaction; the composite material is then uniformly mixed with a lithium source and a doping additive containing an M element according to a stoichiometric ratio, and then sintered for a second time to obtain the sodium ion battery positive electrode material.

6. The method for preparing a positive electrode material for a sodium ion battery according to claim 5, characterized in that: The doping additive containing the M element is one or more of lanthanum trioxide, titanium dioxide, silicon dioxide, zirconium dioxide, niobium pentoxide, and tantalum pentoxide.

7. The method for preparing a positive electrode material for a sodium ion battery according to claim 5, characterized in that: The sintering temperature of the first sintering and the second sintering is 800-1000° C., and the sintering time is 6-18 hours.

8. A positive electrode sheet, characterized in that: The positive electrode active slurry in the positive electrode plate includes the sodium ion battery positive electrode material according to any one of claims 1 to 4.

9. A sodium ion battery, characterized in that: Comprising the positive electrode sheet as described in claim 8.

Citation Information

Patent Citations

  • Positive electrode material, preparation method thereof and battery

    CN115566183A

  • Coated sodium-based layered oxide composite material, preparation method thereof and sodium ion battery

    CN116826014A

Cited By

  • Sodium-ion battery positive electrode material, preparation method thereof and sodium-ion battery

    CN120998989A